PENGARUH BERMAIN SIANIDA (SUARA, IRAMA, DAN NADA) TERHADAP KECERDASAN MUSIK ANAK USIA DINI - Yenni Okta Prasetya; Dzikrotul Chulwah; Nur Lailatul Mubarokah; Veny Iswantiningtyas (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
This study aims to investigate the effect of playing sianida (sound, rhythm and tone) in improving the musical intelligence of early childhood in Dharma Wanita VI Kepung Kindergarten Kepung Subdistrict Kediri. The research method used the Nonequevalent control Group Design, in this design the control group experimental group was not chosen randomly. The experimental group consisted of 18 children and a control group of 20 children. Data collection techniques used  were  pretest and posttest, while data analysis techniques inferential statistic. The results showed significant effect of playing sianida(sound, rhythm and tone)  on early childhood musical intelligence. The results of the study can be used as a  recommendation to kindergarten owners to use sianida to improve early childhood music intelligence’